Handbook of Word-Formation
XVIII, 470 p.
Keywords: This volume, intended both for advanced students and scholars of linguistics, traces the many strands of study in the field of word formation that have developed since the seminal work of Marchand and Lees in the 1960s. In mapping the state of the art in the field of word formation, it avoids a biased approach by presenting different, but mutually complementary frameworks within which research into word formation has taken place. It covers the historical development of theories of word formation within generative grammar, and affords a solid introduction to the treatment of word formation in cognitive grammar, natural morphology, optimality theory, Lexeme Morpheme Base Morphology, onomasiological theory, and other recent frameworks. Each topic is presented by an expert who has contributed significantly to the field. In addition to surveying theoretical developments from both European and North American perspectives, it looks specifically at individual English word formation processes (derivation, compounding, conversion) and reviews some of the ways in which they have been analyzed since Marchand’s comprehensive treatment nearly five decades ago.